Influência da amônia e oxigênio da água in vivo e da erva-mate ex vivo sobre a estabilidade lipídica de filés de dourado - Veeck, Ana Paula de Lima (2008)
This work was aimed at evaluating the effect of the exposure to stressing ammonia and oxygen levels in vivo as well as the effect of the treatment with erva-mate extract (Ilex paraguariensis) post mortem on the lipid stability of fillets of dourado (Salminus brasiliensis). The influence of different levels of ammonia and oxygen on the proximate composition, fatty acid composition and lipid peroxidation of dourado fillets, as well as on the stability of these fillets during the frozen storage (12 months at -7±1oC) was evaluated. The effect of erva-mate extract on lipid and colour changes of raw fillets of dourado during the frozen storage and on the sensory characteristics and lipid oxidation of cooked dourado fillets during chilled storage was also evaluated. The exposure of dourado during 15 days at high ammonia concentration (0.1 mg/L) affected the composition of fillets, while the exposure to high oxygen (> 6.0 mg/L) increased the value of thiobarbituric acid reactive substances (TBARS) measured immediately after slaughtering. However, the in vivo exposure to stressing ammonia and oxygen levels for 12 hours, did not change TBARS formation during the frozen storage. A 12-hours exposure to high ammonia increased the susceptibility of fillets to lipid oxidation during the frozen storage (higher conjugated dienes and peroxides values). On the other hand, the exposure to low oxygen concentration (4.5 mg/L) did not increase the lipid oxidation of fillets. The aqueous 10% (w/v) erva-mate extract had an antioxidant capacity equivalent to 25.8 mg trolox/mL extract in the DPPH radical scavenging assay. The treatment of dourado fillets with this extract (fillets dipped in the extract for 1 min) reduced the colour changes during frozen storage (lower changes in luminosity and hue values) and the fillets treated with erva-mate extract had lower increase of free fatty acids, conjugated dienes and TBARS values during the frozen storage (12 meses at - 7±1oC). The treatment of dourado fillets with aqueous crude 10 or 20% erva-mate extract did not modify the taste, but caused important changes in the colour (decrease of luminosity and increase in the yellowness) of cooked dourado fillets. Since crude erva-mate extract changed the colour, it was decided to purify the extract in order to eliminate chlorophyll and other pigments. Liquid-liquid partition yielded a clear upper phase with antioxidant activity in the DPPH radical scavenging assay (1.2 vs. 0.7 mg trolox equivalents/ml extract, upper phase vs. lower phase). The purified erva-mate extract reduced peroxides, but had no significant effect on the content of TBARS of cooked dourado fillets during chilled storage (6 dias at 7±1oC). No effect of ammonia or oxygen was observed on the fatty acid composition. Similarly, there was no effect of the frozen storage or of the treatment with erva-mate extract. The results indicate that the exposure to high ammonia levels increased the susceptibility of fillets to lipid oxidation during the frozen storage. In addition, ervamate had antioxidant activity in frozen fillets and some protective effect against lipid oxidation of cooked dourado fillets under chilling storage. This demonstrates the possible use of erva-mate to extend the shelf-life of fish fillets.